Tourism in digital era : the influence of digital marketing on the intention to visit museum - Jasmine Rahma Amalia,; Ita Musfirowati Hanika, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The growth of digital media usage in tourism industry over the last decade all over the world has led Menteri Pariwisata dan Industri Kreatif Republik Indonesia (the Ministry of Tourism and Creative Economy of the Republic of Indonesia) to establish tourism digital marketing as one of national tourism development master plans from 2010 to 2025. It was noticed that a tourism development vision could be pursued by achieving several goals, such as developing synergistic, excellent and responsible tourism marketing to increase domestic tourist visits. To implement the master plan and to gain more visitors, most of the tourism sectors including museums have increasingly utilised digital media. As one of the favourite museums in DKI Jakarta, Bank Indonesia Museum has engaged the visitors through Instagram and Electronic Word of Mouth (E-Wom). The objective of this study is to explore the influence of Instagram @museum_bi posts and E-WOM on the intention to visit the Bank Indonesia Museum. The method used was empirically verified through a survey which was distributed to Instagram followers of @museum_bi and analysed with SPSS. The results of this study revealed that the spread of Instagram @museum_bi posts, electronic word of mouth, and the posts of Instagram @museum_bi and electronic word of mouth simultaneously influenced tourists’ intentions to visit the Bank Indonesia Museum.